Ochratoxins’ Effects on the Functional Properties and Nutritional Compositions of Grains - Chinaza Godswill Awuchi; Ifeanyi Owuamanam; Chika Ogueke (Newinera Publisher, 2021)
This study assessed the effects of total ochratoxins on the nutritional composition and functional properties of grain flours. The grains cowpea, sorghum, maize, groundnut, rice, millet, and acha were milled. The proximate composition, functional properties, as well as Total Ochratoxin levels, were determined. The effects of the Ochratoxins on the nutritional and functional properties of the grains were evaluated. Ochratoxin levels in grain flours ranged from 0.09 to 54.41 μg/kg and not seen in some rice samples. Most Total Ochratoxin levels found in the grains were beyond the WHO/EU/FAO permissible limit, 5.00 µg/kg. Groundnut and Cowpea have a significant high content of protein and fiber. Groundnut had the highest average fat content, 41.84 %. The ash content of the grains ranged from 0.73 to 3.61%. The presence of ochratoxins had a significant impact on the grain's carbohydrates, proteins, and fat. Their presence had moderate effects on crude fiber, ash, and functional properties and negligible effect on grain moisture.